Construction and demolition waste recycling and reuse clause in standard form contracts: impact on project performance - Nurhaizan, Mohd Zainudin; Ahmad Amir, Hafiz Ahmad; Rahimi, A. Rahman; Fadzida, Ismail (Edward Elgar Publishing, 2023)
In recent years, the generation of construction and demolition waste (CDW) has increased tremendously and posed multiple threats to the economy, environment, and sustainability. The alarming rise of CDW generation can be attributed to urbanization and extensive infrastructure and reconstruction projects (Jain, 2021). Relatively in the European Union, CDW comprises the largest waste stream with stable amounts produced over time (EEA, 2020). If not treated, CDW could negatively affect the environment, leading to severe air pollution and increased concentrations of particulate matter and aerosols (Swarna, Tezeswi, & Siva Kumar, 2022).